Improvement of mechanical properties of polylactic acid adhesion joints with bio‐based adhesives by using air atmospheric plasma treatment. Issue 32 (14th May 2015) - Jordá‐Vilaplana, Amparo; Sánchez‐Nácher, Lourdes; Fombuena, Vicent; García‐García, Daniel; Carbonell‐Verdú, Alfredo
ABSTRACT The packaging industry generates a high volume of wastes; so that, there is a high demand of biodegradable materials, which do not damage the environment. Nowadays, there is an interesting consumption of polylactic acid (PLA) due to its biodegradable features. This work focuses on the improvement of mechanical properties of PLA adhesion joints for uses in the packaging industry. In order to achieve that purpose, atmospheric plasma treatment is used to selectively modify PLA surface properties. The obtained experimental results show that the atmospheric plasma treatment is suitable to increase the mechanical performance of PLA–PLA adhesive joints. Optimum conditions for the atmospheric plasma treatment were obtained with a nozzle–substrate distance of 10 mm and an advance rate in the 100–300 mm s−1 range; for these particular conditions, the effectiveness of the surface modification is the highest. The main plasma‐acting mechanisms are microetching together with the insertion of polar groups which lead to an interesting synergy that causes a remarkable increase in mechanical properties of adhesion joints. In particular, the shear strength of untreated PLA–PLA adhesion joints is close to 50 N cm−2 and this value is increased up to values of about 168.7 N cm−2 with optimum plasma treatment conditions. This indicates that atmospheric plasma treatment is both a technical and an environmental friendly technique to improve mechanical performance of PLA adhesive joints. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42391.